2013
DOI: 10.1186/1471-2334-13-380
|View full text |Cite
|
Sign up to set email alerts
|

Trough colistin plasma level is an independent risk factor for nephrotoxicity: a prospective observational cohort study

Abstract: BackgroundData regarding the most efficacious and least toxic schedules for the use of colistin are scarce. The aim of this study was to determine the incidence and the potential risk factors of colistin-associated nephrotoxicity including colistin plasma levels.MethodsA prospective observational cohort study was conducted for over one year in patients receiving intravenous colistin methanesulfonate sodium (CMS). Blood samples for colistin plasma levels were collected immediately before (Cmin) and 30 minutes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
208
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(235 citation statements)
references
References 31 publications
12
208
3
7
Order By: Relevance
“…Some recent studies have investigated the risk factors for colistin-associated NT (8,21,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Results from previous studies are given with their significance levels in Table 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have investigated the risk factors for colistin-associated NT (8,21,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Results from previous studies are given with their significance levels in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Two large studies demonstrated that patients with septic shock had a higher incidence of NT (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The rates of colistin-induced AKI reported in the literature vary between 11z and 53.5z (3,4,6,9,10,(13)(14)(15)(16)(17). This variability could be attributed to the dose and duration of the therapies, and to the varying definitions of AKI.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of renal toxicity is not exactly clear, but proximal tubulopathy and mammalian uroepithelium toxicity were observed in some studies. It has been reported that the nephrotoxicity of colistin is generally mild and reversible (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective observational cohort study demonstrated that trough plasma levels of colistin is an independent risk factor for nephrotoxicity 13) and that trough plasma colistin levels of 3.33 mg/L on day 7 best predicted acute kidney injury (AKI). Information on the plasma levels of colistin will be helpful for future dosing recommendations.…”
Section: Clinical Course Of This Casementioning
confidence: 99%